2011
DOI: 10.2106/jbjs.j.01998
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Factors Influencing the Decision to Have an Elective Amputation

Abstract: The severity of pain and the desire for improved function are strong drivers for patients deciding to undergo elective amputation of a functionally impaired lower extremity. While patients do not want others' opinions, information regarding life with an amputation helps to set realistic expectations regarding outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…First, we have a relatively small sample of patients though it is within the range of other studies investigating similar topics. 16 Second, our sample is relatively educated and included no minority patients. Therefore, the generalizability to all patients may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…First, we have a relatively small sample of patients though it is within the range of other studies investigating similar topics. 16 Second, our sample is relatively educated and included no minority patients. Therefore, the generalizability to all patients may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the limitations of quantitative approaches to these and other topic areas, health and disability researchers have begun to use qualitative research methods to identify what the meanings of ill health and disability are from the point of view of those concerned. With particular regard to the topics of amputation and prosthesis use, qualitative research has been useful in deepening an understanding of a number of complex areas including factors influencing the decision to have an elective amputation [9], the experiences of prosthetic prescription by lower limb prosthetic users [10], the management of amputation-related pain [11], and communication difficulties with prosthetists [12].…”
Section: Review Articlementioning
confidence: 99%
“…Previous studies have shown that the collaborative process of medical decision-making between patients and their physicians is influenced by a variety of factors, such as individual patient and family experiences, and the opinions of family, friends, or other knowledgeable parties. 10,11 For elective reconstructive procedures aimed solely at improving quality of life (rather than increasing life expectancy), the concept of risk-benefit is often more individualized and varied according to patient specific desires and values. 11,12 Thus, among these interventions, it is imperative to understand the motivations, preferences, and expectations that drive medical decision-making in order to maximize the likelihood of patient satisfaction and improved outcomes.…”
mentioning
confidence: 99%